Gelatin/PLA-loaded gold nanocomposites synthesis using Syzygium cumini fruit extract and their antioxidant, antibacterial, anti-inflammatory, antidiabetic and anti-Alzheimer’s activities - Manickam Rajkumar; S. I. Davis Presley; Nathiya Thiyagarajulu; Koyeli Girigoswami; Gopalarethinam Janani; Chinnaperumal Kamaraj; Bharathi Madheswaran; Bhupendra Prajapati; Nemat Ali; Mohammad Rashid Khan (Scientific Reports)
Abstract Nanotechnology has experienced significant advancements, attracting considerable attention in various biomedical applications. This innovative study synthesizes and characterizes Ge/PLA/AuNCs (gelatin/PLA/gold nanocomposites) using Syzygium cumini extract to evaluate their various biomedical applications. The UV–Visible spectroscopy results in an absorption peak at 534 nm were primarily confirmed by Ge/PLA/AuNCs synthesis. The FTIR spectrum showed various functional groups and the XRD patterns confirmed the crystalline shape and structure of nanocomposites. The FESEM and HRTEM results showed a oval shape of Ge/PLA/AuNCs with an average particle size of 21 nm. The Ge/PLA/AuNC’s remarkable antioxidant activity, as evidenced by DPPH (70.84 ± 1.64%), ABTS activity (86.17 ± 1.96%), and reducing power activity (78.42 ± 1.48%) at a concentration of 100 μg/mL was observed. The zone of inhibition against Staphylococcus aureus (19.45 ± 0.89 mm) and Echericia coli (20.83 ± 0.97 mm) revealed the excellent antibacterial activity of Ge/PLA/AuNCs. The anti-diabetic activity of Ge/PLA/AuNCs was supported by inhibition of α-amylase (82.56 ± 1.49%) and α-glucosidase (80.27 ± 1.57%). The anti-Alzheimer activity was confirmed by inhibition of the AChE (76.37 ± 1.18%) and BChE (85.94 ± 1.38%) enzymes. In vivo studies of zebrafish embryos showed that Ge/PLA/AuNCs have excellent biocompatibility and nontoxicity. The SH-SY5Y cell line study demonstrated improved cell viability (95.27 ± 1.62%) and enhanced neuronal cell growth following Ge/PLA/AuNCs treatment. In conclusion, the present study highlights the cost-effective and non-toxic properties of Ge/PLA/AuNCs. Furthermore, it presents an attractive and promising approach for various future biomedical applications.